2020
DOI: 10.1017/s0022215120002467
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and taste dysfunction in coronavirus disease 2019 patients: its prevalence and outcomes

Abstract: Objectives. To evaluate the occurrence, clinical course and outcomes of olfactory and gustatory dysfunction in patients with laboratory confirmed coronavirus disease 2019 infection. Methods. This is a prospective cross-sectional study of patients diagnosed with coronavirus disease 2019 infection by reverse transcription polymerase chain reaction over two months. The epidemiological and clinical outcomes studied were: age, sex, general symptoms, and olfactory and taste dysfunction. Results. A total of 410 coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
0
20
1
1
Order By: Relevance
“…In adults, anosmia and dysgeusia in COVID-19 patients has been widely reported in literature with a varying prevalence. There is a difference in the prevalence of olfactory and taste dysfunction between the Asian 14 , 15 , 16 and European population 17 , 18 , 19 , 20 , 21 , 22 . This may be due to increased expression of ACE2 in the European population as compared to the Asian population 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, anosmia and dysgeusia in COVID-19 patients has been widely reported in literature with a varying prevalence. There is a difference in the prevalence of olfactory and taste dysfunction between the Asian 14 , 15 , 16 and European population 17 , 18 , 19 , 20 , 21 , 22 . This may be due to increased expression of ACE2 in the European population as compared to the Asian population 23 .…”
Section: Discussionmentioning
confidence: 99%
“…This rapid and spontaneous recovery of OTD has also been reported in adult COVID-19 patients. Some studies report that chemosensory loss in COVID-19 adult patients recovers in about 1-2 weeks of onset, in conjunction with improvement of infection 14 , 17 . This short duration and spontaneous recovery supports the findings that SARS-CoV-2 targets the non neural olfactory epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…An expert who carried out animal experiments has confirmed that coronavirus is highly neurotropic and can directly affect olfactory neurons, which might be another fundamental cause of olfactory dysfunctions induced by the novel coronavirus [ 70 ]. When the potential target of SARS-CoV-2 is located in non-neuro-olfactory epithelial cells, the patient's olfactory function often recovers within 2 to 4 weeks [ 71 ]. Significantly, once the virus infects olfactory stem cells, such as horizontal basal cells, it can cause long-term olfactory dysfunctions [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 This supplements and complements recent articles in The Journal on acute care, by Osborne and colleagues, 8 on ethics, by Leonard, 9 and on smell and taste dysfunction, by Jain and colleagues. 10…”
mentioning
confidence: 99%